The Feasibility of Telephone-delivered Self-management Intervention in Multiple Sclerosis - Mozaffar Hosseininezhad; Sajjad Saadat; Fatemeh Younesi Rostami; Roghaye Zare; Ali Bonyad; Masoumeh Qanbary Joopish; Alia saberi; Fateme Shafaee (Caspian Journal of Neurological Sciences)
Background: Self-management plays a significant role in people’s active participation in treating multiple sclerosis (MS), improving quality of life, suppressing symptoms, and reducing treatment costs. People with MS face many physical, mental and emotional challenges that negatively affect their quality of life. Objectives: This study aims to determine the feasibility of telephone-delivered self-management intervention in people with MS. Materials & Methods: This quasi-experimental study employed a pretest-posttest and a two-month follow-up design. A total of 20 MS patients registered in the nationwide MS registry of Iran (NMSRI), Guilan, in 2020 took part in this study. The participants were selected through a public callback using judgmental sampling. The telephone-delivered self-management intervention, delivered through educational video files and telephone calls, included evidence-based cognitive behavioral therapy and psychological strategies to assist participants. The intervention was delivered in 8 weekly sessions. The MS self-management scale–revised (MSSM-R) and the short-form health survey (SF-36) were used to collect study data. Results: The participants had a disproportionate distribution in gender, marital status, place of residence, employment status, and income. The intervention affects the self-management total score (P<0.001), the treatment adherence/barriers subscale (P=0.024), the MS knowledge and information subscale (P<0.001), and health maintenance behavior (P=0.004). It also influenced the quality-of-life total score (P=0.049) and mental health domain (P=0.018). Conclusion: Telephone-delivered self-management intervention in patients with MS has positive effects in many of the investigated areas, and this intervention can be used to improve the quality of life of these patients.